1989
DOI: 10.1111/j.1399-6576.1989.tb02854.x
|View full text |Cite
|
Sign up to set email alerts
|

Flumazenil used for antagonizing the central effects of midazolam and diazepam in outpatients

Abstract: In a double-blind, randomized trial, the efficacy and safety of flumazenil, a benzodiazepine antagonist, was evaluated in patients after gastroscopy under midazolam or diazepam sedation. The criteria of efficacy were the degree of sedation and anterograde amnesia. Flumazenil significantly reduced the degree of sedation in both groups without significant intergroup differences. No sign of resedation was found during the observation period of 3 h. The anterograde amnesia was effectively antagonized in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In previous reports, resedation was not observed when the sedation level was assessed by the investigator's subjective assessment. 14,15 However, in psychomotor tests, impairments were observed even 3 hours after the administration of flumazenil. 16,17 It was also reported that standing independently was more sensitive than both spontaneous eye opening and response to a verbal command.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, resedation was not observed when the sedation level was assessed by the investigator's subjective assessment. 14,15 However, in psychomotor tests, impairments were observed even 3 hours after the administration of flumazenil. 16,17 It was also reported that standing independently was more sensitive than both spontaneous eye opening and response to a verbal command.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significantly faster recovery of the patients after the injection of flumazenil than after placebo. Patients were awake shortly after flumazenil, but remained drowsy or asleep after placebo administration (164,165). By contrast, another placebo-controlled randomized trial including patients undergoing upper gastrointestinal endoscopy under diazepam sedation reported no significant differences between groups with regard to either…”
Section: Sedation During Upper Gastro-intestinal Endoscopymentioning
confidence: 94%
“…An initial dose of 0.2-0.5 mg iv followed by doses of 0.1-0.2 mg every minute until the patient is awake or to a total dose of I mg significantly reduces the degree of sedation common to patients sedated or anesthetized with BZDs. 32,34,38,39,[45][46][47] Failure of a patient with unconsciousness of unknown origin to respond to intravenous doses of ftumazenil >5 mg may indicate the involvement of agents other than BZDs, or the presence of another etiology. Once administered, the duration of a single dose offtumazenil should not be expected to exceed one hour, For cases in which prolonged activity is desired, either repeated intravenous administration or the initiation of an infusion (0.1-0.5 mg/h) may be implemented.v-P-"…”
Section: Drug Doseand Administrationmentioning
confidence: 99%